Evidence Based Practice in Using Antibiotics for Acute Tonsillitis in Primary Care Practice - Nejashmikj, Valentina Risteska; Stojkovska, Snezhana; Kondova Topuzovska, Irena; Stavrikj, Katarina (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/Sciendo, 2017)
The increased use of antibiotics for acute tonsillitis is a public health problem. 80% of the antibiotic prescriptions for acute tonsillitis are done in the Primary Care practice (PCP). The inappropriate use of the antibiotic causes bacterial resistance and treatment failure. Only patients with acute tonsillitis caused by Group A beta-hemolytic streptococcus (GAS) have benefit of the antibiotic treatment, which is a predict cause in 5-20%. In order to assess the antibiotic prescribing for acute tonsillitis by the doctors in the PCP in Macedonia we use the data from the national project about antibiotic prescribing for acute respiratory tract infections which was conducted in November 2014 during a period of 4 weeks as part of the E-quality program sponsored by the IPCRG. 86 general practitioners from Macedonia have participated. The group of 1768 patients, from 4 months to 88 years of age, with diagnosis of acute tonsillitis was analyzed. The antibiotic prescriptions according to the Centor score criteria were compared to the Cochran's guidelines which are translated and recommended as national guidelines. 88.8% of the patients with acute tonsillitis were treated with antibiotics, of which 52.9% with Centor score 0 to 2 were treated inappropriate. The diagnosis is mostly made based on the clinical picture and the symptoms. Only (23.6%) of the patients were treated with antibiotics (Penicillin V and cephalexin) according to the guidelines. We concluded that there is a low adherence to the national guidelines. The clinical assessment is not accurate in determining the etiology. Also, there is a high nonadherence in prescribing the first choice of antibiotics. We emphasize the need to change the general practitioners' prescription behavior according to the guidelines.